Formation of the main approaches to the classification of competitiveness (Путеводитель предпринимателя)
This article discusses the concept of «competition» and «competitiveness». A brief overview of the key factors necessary for the successful operation and development of enterprises in various sectors in crisis and transition to a market economy. Explore the growing role of the competitive position of the company in the contemporary economy.